Calculation of coal resources and reserves using the cross-section method in the mining plan area of PT. Sentosa Prima Coal in Mersam District, Batang Hari District, Jambi - Muhammad Jundi Haikal Azis; Yazid Fanani (Journal of Earth and Marine Technology (JEMT), 2022)
PT. Sentosa Prima Coal is a company engaged in the Coal sector. This company is located in Mersam District, Batanghari Regency, Jambi Province. The area of the mining business permit of PT. Sentosa Prima Coal of 2000 Ha. Mining activities require reserve calculations before mining activities are carried out, including making a coal deposit model, calculating coal resources, pit design, calculating coal reserves, and calculating the stripping ratio (SR) value, so that later the number of coal reserves can be obtained and obtain a deposit model. The modeling and calculation of reserves were carried out using the "cross-section" with the help of Surpac 6.6.2 software. Based on the Cross Section's estimation results, coal resources for PT. Sentosa Prima Coal amounted to 8,073,932 tons, and coal reserves 6,662,514 tons, the volume of Overburden for the planned mining activity area was 24,779,981 BCM, and the stripping ratio value was obtained 1:4.